2010
DOI: 10.1159/000313773
|View full text |Cite
|
Sign up to set email alerts
|

Blood Purification in Sepsis: A New Paradigm

Abstract: Sepsis is one of the main causes of death in critically ill patients. The pathophysiology of sepsis is complex and not completely understood. The proinflammatory and anti-inflammatory response leads to cell and organ dysfunction and, in many cases, death. Thus, the goal of the intervention is to restore the homeostasis of circulating mediators rather than to inhibit selectively the proinflammatory or anti-inflammatory mediators. Blood purification has been reported to remove a wide array of inflammatory mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 9 publications
0
63
0
3
Order By: Relevance
“…Finally, Peng and colleagues [12] recently suggested that blood purification therapies act at the inflammatory cell level to restore the immune function through the regulation of monocytes, neutrophils, or even lymphocytes. This theory is supported by recent studies [13,14].…”
Section: Concept Of Blood Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Peng and colleagues [12] recently suggested that blood purification therapies act at the inflammatory cell level to restore the immune function through the regulation of monocytes, neutrophils, or even lymphocytes. This theory is supported by recent studies [13,14].…”
Section: Concept Of Blood Purificationmentioning
confidence: 99%
“…If this 'cellular level' theory with immune response restoration is confirmed, timing indications for blood purification would need to be reconsidered since optimal timing for initiating a blood purification therapy would not be only in the early phase of septic shock as it is suggested today. Furthermore, a novel component of this hypothesis is that, by removing mediators from the plasma in the setting of systemic inflammation, one can restore the concentration gradient from plasma to infected tissues [12]. This gradient has significant effects on leukocyte tracking and bacterial clearance [14].…”
Section: Concept Of Blood Purificationmentioning
confidence: 99%
“…Furthermore, the reduction in the circulating level of molecules could restore the concentration gradient necessary to guide the reticuloendothelial system to the main production site (i.e., the source of infection) improving the efficiency of the immune system (‘cytokinetic model') [8]. Finally, a direct immune-homeostatic role has been demonstrated for some extracorporeal blood purification therapies that modulate the HLA-DR expression, correlating with cell activation and interaction with some cell reproductive systems [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies on active interventions for sepsis using continuous blood purification (CBP) have been reported in China and internationally. CBP has been shown to prevent and treat severe sepsis (Peng et al, 2010). During treatment of sepsis, CBP lowers the overall in vivo peak concentration of inflammatory mediators, down-regulates the body's inflammatory response.…”
Section: Introductionmentioning
confidence: 99%